Value Of Religiusity In The Mujahadah Tradition; Study at Ulul Albab Nganjuk Islamic Vocational School - Hilma Dian Wulandari; A. Jauhar Fuad (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2020)
This paper aims to examine the values ​​of religiosity through the mujahadah tradition at Islamic Vocational School Ulul Albab Nganjuk. This research departs from two research questions, "How is the mujahadah tradition in Ulul Albab Nganjuk Islamic Vocational School? What are the religious values ​​contained in the mujahadah tradition at SMK Islam Ulul Albab Nganjuk?". This research is a qualitative research with a phenomenological approach. This research conducted in Ulul Albab Islamic Vocational School. Data collection techniques using in-depth interviews and partisipan observation. With these two questions, the results of the study found that (1) the mujahadah tradition is a behavior to fight lust, as an effort to combat all bad attitudes caused by lust of anger. Meanwhile, the mujahadah tradition at Ulul Albab Islamic Vocational School contains the recitation of Hizbul Quran and Rotib Hadad, then continued with sunnah prayers, reading rotib istigasah then tausiyah after that it is continued with dhuhur prayer in congregation and ends with mushofahah. (2) Mujahadah which is held at Ulul Albab Islamic Vocational School is intended so that all students can become better individuals and so that their spiritual souls can increase, and also so that their spirituality will mature. The results of observations on the implementation of the mujahadah at Ulul Albab Islamic Vocational School show that students' awareness of the importance of the mujahada is still lacking, but in its implementation they are very enthusiastic and happy in doing it, although the changes seen are still not optimal.